Thermodynamic constraints and the evolution of parental provisioning in vertebrates. (27th March 2019) - Beekman, Madeleine; Thompson, Michael; Jusup, Marko
Abstract: Why is postnatal parental provisioning so rare in ectothermic vertebrates while prolonged parental care is almost ubiquitous in endotherms? We argue that the scarcity of postnatal parental care is a result of ectothermy itself. While almost all endothermic young require prolonged postnatal care due to thermal constraints, ectothermic physiology does not pose the same constraint. Most ectothermic young are thus independent from birth. Ectothermic mothers are better off investing in future reproductive events than to continue investing into independent young, because the cost of feeding young does not outweigh the benefits. Ectothermy further releases the constraint on offspring size resulting in offspring of ectothermic vertebrates often being much smaller than their parents. When parents and offspring differ greatly in size, both tend to specialize on different diets, making the feeding of young by much larger individuals not impossible, but less likely. Additionally, when the size difference between parents and offspring is significant, both are likely to live in different habitats. Such spatial segregation is also less conducive to the evolution of parental care. In those species where parents and offspring are not spatially separated and parental care does occur, it is mainly restricted to the guarding of eggs or juveniles; parents of very few species provide their offspring with food. We conclude that parental care beyond the guarding of eggs or young is much less likely to evolve in ectothermic vertebrates compared with endothermic vertebrates, unless there are exceptional circumstances that strongly select for parents to provide for their offspring.